2022
DOI: 10.1158/1078-0432.ccr-22-0562
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Occult Recurrence Using Circulating Tumor Tissue Modified Viral HPV DNA among Patients Treated for HPV-Driven Oropharyngeal Carcinoma

Abstract: Purpose: Despite generally favorable outcomes, 15-25% of patients with HPV-driven oropharyngeal squamous cell carcinoma (OPSCC) will recur. Current post-treatment surveillance practices rely on physical exams and imaging and are inconsistently applied. We assessed circulating tumor tissue modified viral (TTMV)-HPV DNA obtained during routine post-treatment surveillance among a large population of real-world patients. Experimental Design: This retrospective clinical case series included 1076 consecutive patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
79
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(82 citation statements)
references
References 45 publications
(21 reference statements)
1
79
0
2
Order By: Relevance
“…Finally, circulating tumor HPV (ctHPV) DNA shows promise in both detection and surveillance of HPV-positive oropharyngeal cancer ( 59 61 ). By targeting E6 and/or E7 oncogenes, plasma ctHPV DNA can be measured with PCR or next generation sequencing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, circulating tumor HPV (ctHPV) DNA shows promise in both detection and surveillance of HPV-positive oropharyngeal cancer ( 59 61 ). By targeting E6 and/or E7 oncogenes, plasma ctHPV DNA can be measured with PCR or next generation sequencing.…”
Section: Discussionmentioning
confidence: 99%
“…with two consecutive positive tests strongly predicting disease recurrence ( 60 ). Clearance kinetics suggest that in low risk patients, ctHPV DNA rapidly decreases to <1 copy/mL by the first postoperative day ( 61 , 62 ). Therefore, elevated levels are associated with risk of residual disease and could be used as a biomarker for selecting adjuvant therapy in future surgical clinical trial design.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study on 93 patients with HPV-positive oropharynx carcinoma, the presence of combined salivary and plasma HPV DNA after radical treatment was 91% specific and 70% sensitive in predicting recurrence within 3 years [ 80 ]. A multicenter study of 1076 HPV-positive oropharyngeal carcinoma from 108 institutions in the United States showed that ct-HPV DNA was able to identify 96% cases with occult recurrence [ 90 ]. Therefore, emerging evidence supports the promising role of these biomarkers for early cancer detection, tumor mutational burden evaluation and post-treatment surveillance, and are currently being investigated [ 80 , 91 ].…”
Section: Optimizing Surveillance Protocolsmentioning
confidence: 99%
“…15 Studies to date have primarily evaluated the utility of qPCR or ddPCR in analysing HPV ctDNA in the plasma, serum and saliva of patients with head and neck cancers (Table 1). [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] Over the years, numerous assays have been developed to measure HPV ctDNA in patients with HPV-positive head and neck carcinoma with varying sensitivity and specificity. One of the early studies using qPCR, Cao et al, found detectable HPV ctDNA in 65% of the pretreatment plasma samples of 40 patients with HPV-positive oropharyngeal carcinoma.…”
Section: Analysis Of Human Papillomavirus Circulating Tumour Dnamentioning
confidence: 99%
“…45 HPV ctDNA analysis is sensitive in detecting recurrence with promise for clinical application in surveillance. 29,30 One retrospective study by Berger et al evaluated the utility of HPV ctDNA as a biomarker of recurrent disease in 1,076 patients with HPV-positive OPSCC. 30 Eighty patients (7.4%) had at least one positive HPV ctDNA.…”
Section: Post-treatment Human Papillomavirus Circulating Tumour Dna A...mentioning
confidence: 99%